2020
DOI: 10.1038/s41417-020-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

EPHA5 mutation predicts the durable clinical benefit of immune checkpoint inhibitors in patients with lung adenocarcinoma

Abstract: Background: Immune checkpoint inhibitor (ICI) therapy has shown remarkable clinical benefit in lung adenocarcinoma (LUAD) patients. Genomic mutations may be applicable to predict the response to ICIs. Eph receptor A5 (EPHA5) is frequently mutated in breast cancer, lung cancer and other tumors; however, its association with outcome in patients who receive immunotherapy remains unknown. Methods: Somatic mutation data, gene expression data and clinicopathologic information were curated from patients with LUAD who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…Huang et al demonstrated that EPHA5 ‐mutated lung adenocarcinomas had durable responses to immunotherapy likely related to alterations in the DDR pathway, increased tumor mutational burden, and a favorable antitumor immune signature [20]. We found similar results in our exceptional responders.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Huang et al demonstrated that EPHA5 ‐mutated lung adenocarcinomas had durable responses to immunotherapy likely related to alterations in the DDR pathway, increased tumor mutational burden, and a favorable antitumor immune signature [20]. We found similar results in our exceptional responders.…”
Section: Discussionsupporting
confidence: 82%
“…Eph receptors are the largest family of receptor tyrosine kinases and are known to play an important role in tumor immunity by regulating chemotaxis and migration and enhancement of CD8+ T‐cell activity against tumor cells [16–19]. A recently study showed that EPHA5 mutations were associated with increased tumor mutation burden, tumor‐infiltrating lymphocytes, and durable responses in patients with lung adenocarcinoma treated with immunotherapy [20]. This study also reported that EPHA5 ‐mutated tumors were associated with high mutation frequencies of DDR genes and had a tumor microenvironment that was enriched with tumor‐infiltrating CD8+ T cells, CD4+ activated memory T cells, and macrophage M1 cells [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies showed that driver gene mutations may cause differences in the efficacy of ICIs by affecting the tumor immune microenvironment (Huang et al, 2020;Lin W. et al, 2020;Niu et al, 2020;Yi et al, 2020;Zhang et al, 2020). Dong et al (2017a) indicated that non-small cell lung cancer patients with EGFR mutations responded poorly to PD-(L)1 inhibitors, which may be related to reduced CD8 + T lymphocyte infiltration and low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%